2016
DOI: 10.1002/humu.22999
|View full text |Cite
|
Sign up to set email alerts
|

DNA Diagnostics of Hereditary Hearing Loss: A Targeted Resequencing Approach Combined with a Mutation Classification System

Abstract: Although there are nearly 100 different causative genes identified for nonsyndromic hearing loss (NSHL), Sanger sequencing-based DNA diagnostics usually only analyses three, namely, GJB2, SLC26A4, and OTOF. As this is seen as inadequate, there is a need for high-throughput diagnostic methods to detect disease-causing variations, including single-nucleotide variations (SNVs), insertions/deletions (Indels), and copy-number variations (CNVs). In this study, a targeted resequencing panel for hearing loss was devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 47 publications
(56 reference statements)
4
50
1
3
Order By: Relevance
“…[28][29][30][31][32][33][34] A relatively high frequency of STRC deletions was found in our Dutch population (2%), as has also been reported in other populations. 8,9 In one case (ISO31), we found causative variants in a gene that is associated with an identifiable phenotype and segregating with a recessive inheritance pattern.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…[28][29][30][31][32][33][34] A relatively high frequency of STRC deletions was found in our Dutch population (2%), as has also been reported in other populations. 8,9 In one case (ISO31), we found causative variants in a gene that is associated with an identifiable phenotype and segregating with a recessive inheritance pattern.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies using massively parallel sequencing have reported similar overall diagnostic rates, despite of using different technologies and testing different populations. [32][33][34]37,38 We found that causative variants in GJB2, USH2A, MYO6, STRC and MYO15A underlie HI in 14.0% of the cases in our cohort. This is in agreement with the previously published studies on the involvement of HI genes in other populations.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Indeed, coverage of targeted areas was similar or superior to that reported in other gene panels despite the large number of genes covered (Nemeth et al , 2013; Yohe et al , 2015). Moreover, the diagnosis rate in our study was comparable to, or higher than, that reported in similar approaches recently applied in other patient groups exhibiting phenotypic heterogeneity (Kammermeier et al , 2014; Sommen et al , 2016; Trump et al , 2016). …”
Section: Discussionsupporting
confidence: 88%
“…Sommen and colleagues evaluated 131 GJB2 -negative individuals with ARNSHL using a 79-gene panel that included in-house CNV detection and a variant scoring system; they estimated their positive diagnostic rate as ~30% [23*]. Bademci and colleagues investigated 160 multiplex GJB2 -negative ARNSHL families for causative variants in 58 genes and identified a genetic etiology in 90 (56%) families, who segregated likely pathogenic or pathogenic variants in 31 genes [24**].…”
Section: Diagnostic Ratementioning
confidence: 99%